2021
DOI: 10.1371/journal.pone.0254488
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and severity of pneumonia in Indonesian children

Abstract: Objective To determine the prevalence of vitamin D deficiency in Indonesian children hospitalized with pneumonia and evaluate the association between vitamin D status and severity of pneumonia. Methods A hospital-based cross-sectional study was conducted from February 2016 to July 2017 in two district hospitals in Yogyakarta province, Indonesia. Infants and young children aged 2–59 months hospitalized with pneumonia were recruited. Serum blood samples were collected on admission and analyzed for total serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
1
12
0
1
Order By: Relevance
“…We also found 14 articles from citations and hand searching, which resulted in an additional manuscript (15) . Notable exclusions include one study which did not specify the vitamin D cut-off value (34) , one study that included Dutch residents of Indonesian ethnicity (35) , two studies (36,37) that were generated from the same dataset (38) , one poster presentation (39) that were ultimately published as a full A c c e p t e d A r t i c l e paper (40) , and five studies (41)(42)(43)(44)(45) were also excluded as they were part of Southeast Asian Nutrition Surveys (SEANUTS) study (15) . Therefore, seven studies (15,38,40,(46)(47)(48)(49) are available for systematic review and meta-analysis (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…We also found 14 articles from citations and hand searching, which resulted in an additional manuscript (15) . Notable exclusions include one study which did not specify the vitamin D cut-off value (34) , one study that included Dutch residents of Indonesian ethnicity (35) , two studies (36,37) that were generated from the same dataset (38) , one poster presentation (39) that were ultimately published as a full A c c e p t e d A r t i c l e paper (40) , and five studies (41)(42)(43)(44)(45) were also excluded as they were part of Southeast Asian Nutrition Surveys (SEANUTS) study (15) . Therefore, seven studies (15,38,40,(46)(47)(48)(49) are available for systematic review and meta-analysis (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…19 In this study, 16,2 % of pneumonia patients in children under five years old treated at Sadewa Maternal and Child Hospital, Yogyakarta, were malnutrition, and 17,3 % of severe pneumonia were malnutrition, consistent with findings from other studies. 20 Based on previous studies showed that undernutrition is a significant risk factor for severe pneumonia and is related to mortality. It can increase the incidence, severity, and mortality of pneumonia due to weaker host defense mechanisms and impaired respiratory muscle performance.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency is related to several lung pathologies, including respiratory distress syndrome, alveolar inflammation, and epithelial damage. A link between vitamin D status and respiratory morbidity was revealed by several studies on children [ 65 , 66 , 67 ], adults, and the elderly [ 68 , 69 ]. It was clearly demonstrated that low vitamin D status was associated with inflammation in patients with chronic obstructive pulmonary disease (COPD) [ 70 ].…”
Section: Vitamin D Anti-inflammatory Properties: a Role In Inflammato...mentioning
confidence: 99%